The management of information under the optics of complex thought: a reflection - Pinheiro dos Santos, Beatriz Rosa [UNESP]; Pomim Valentim, Marta Ligia [UNESP]; Martins Damian, Ieda Pelogia [UNESP] (Univ Brasilia, Dept Ciencia Informacao, 2020)
The contemporary society immersed in a significant amount of information must integrate the most varied organizational and informational contexts in order to generate knowledge with inter, multi, multi and transdisciplinary characteristics. In this scenario, the information and knowledge produced requires the intervention of complex thinking for the proper valuation and effective development of its processes. In order to contribute to add value to informational processes, the following problem arises: Is it possible to add value to traditional information management practices, through the principles of complex thinking? The aim is to discuss the information management in line with the view of complex thinking. The justification for the development of such research lies in contributing to the theoretical framework of Information Science which, in turn, studies information management in the most varied organizational contexts. Therefore, a literature review was carried out, in which it was possible to verify which aspects of the complex thinking can help in the breaking of paradigms that inhabit the traditional practices coming from different models of information management.
Keywords: Information Management; Theory of Complexity; Complex Thinking